The patient-physician interactions as seen by undergraduate medical students - Kiyohara, Leandro Yoshinobu; Kayano, Lilian Kakumu; Kobayashi, Marcelo Luís Teixeira; Alessi, Mariana Sisto; Yamamoto, Marina Uemori; Yunes-Filho, Paulo Roberto Miziara; Pessoa, Rodrigo Rodrigues; Mandelbaum, Rosana; Okubo, Silvio Tanaka; Watanuki, Thais; Vieira, Joaquim Edson (São Paulo Medical Journal, 2001)
CONTEXT: The interaction between a physician and his or her patient is complex and occurs by means of technical performance and through a personal relationship. OBJECTIVE: To assess the interaction between the medical professional and his or her patient with the participation of medical students assuming a role as observers and participants in a medical appointment in an outpatient office. DESIGN: Questionnaire interview study. SETTING: General Medicine outpatient offices, Hospital das Clínicas, Faculty of Medicine, University of São Paulo. PARTICIPANTS: Medical students performed an ethnographical technique of observation, following 199 outpatient medical appointments with Clinical Medicine Residents. MAIN MEASUREMENTS: A questionnaire filled out by observer students measured the physician’s attitudes towards patients, as well as patients’ expectations regarding the appointment and his or her understanding after its completion. RESULTS: Patients showed higher enthusiasm after the appointment (4.47 ± 0.06 versus 2.62 ± 0.10) (mean ± SEM), as well as some negative remarks such as in relation to the waiting time. The time spent in the consultation was 24.66 ± 4.45 minutes (mean ± SEM) and the waiting time was 123.09 ± 4.91 minutes. The physician’s written orientation was fairly well recalled by the patient when the doctor’s letter could be previously understood. CONCLUSION: Patients benefit from physicians who keep the focus on them. In addition, this program stimulated the students for their accomplishment of the medical course.